IMPLIKASI PELAKSANAAN PENDIDIKAN PRAKARYA DENGAN PRESTASI BELAJAR - Fahmi, Agus (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2018)
A craft education was designed as a communication process of learning to change student behavior becomes fixed, quickly and precisely through craft activities and engineering technology, cultivation technology and management of technology. Students perform the interaction of the work of craft products and technologies dilingkunganya, to be creative to create various types of handicraft products and technology products in order to obtain the perceptual experience of appreciative experience and creativity of the environmental potential. The problem and the aim of this study isunderstanding the implementation of craft education in an effort to increase learning achievement in students. The population is all students of class X in SMAK Kesuma Mataram with the number of students 192 people, while the samples used in this study are some students who have been selected at random sample of 38 students were taken 20% of the total population, the techniques of sampling in this research is technique proportional random sampling. In this study, the data collection methods used method of questionnaire as the principal method while the documentation, observation and interview methods as complementary methods. To analyze the data using the formula t test. The results obtained by analysis of the value t count 13.672and t table value at significance level of 5% with N = 37 is greater than the value of t on the table (13.672 > 2.021) so it can be concluded that these results significantly.Keywords: craft Education, Achievement